2023
DOI: 10.1515/chem-2022-0333
|View full text |Cite
|
Sign up to set email alerts
|

Study on antioxidant and antimicrobial potential of chemically profiled essential oils extracted from Juniperus phoenicea (L.) by use of in vitro and in silico approaches

Abstract: Juniperus phoenicea (L.) is a medicinal plant that has been used in phytotherapy as a treatment of certain pathological infections. In this context, the present work aimed to valorize the essential oil of J. phoenicea seeds (EOGP) by studying its chemical composition, and antioxidant and antimicrobial activities. The EOGP was extracted by use of hydrodistillation and characterized by gas chromatography (GC–MS). The antioxidant power was evaluated by three methods (TAC, DPPH, and FRAP). The antimicrobial power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It is significant to note that the IC50 values in our study were lower than those reported by Fadel et al (51), who found that the extracts of J. Oxycedrus and J. Phoenicea had IC50 values of 0.404 and 0.481 mg/ml, respectively. Rahhal et al (52) observed a similar IC50 level of 0.14 mg/mL for the same species; however, Chelouati et al (13) reported an IC50 level of 0.26 mg/mL for J. phoenicea.…”
Section: Determination Of Antioxidant Activity: Dpph Radical Scavengi...mentioning
confidence: 91%
See 1 more Smart Citation
“…It is significant to note that the IC50 values in our study were lower than those reported by Fadel et al (51), who found that the extracts of J. Oxycedrus and J. Phoenicea had IC50 values of 0.404 and 0.481 mg/ml, respectively. Rahhal et al (52) observed a similar IC50 level of 0.14 mg/mL for the same species; however, Chelouati et al (13) reported an IC50 level of 0.26 mg/mL for J. phoenicea.…”
Section: Determination Of Antioxidant Activity: Dpph Radical Scavengi...mentioning
confidence: 91%
“…Free radicals are very reactive, unstable chemicals that may harm DNA, lipids, proteins, and organisms. By giving electrons or hydrogen atoms to free radicals, antioxidants can neutralize them and shield the organism against oxidative stress and inflammation (13). Natural products, especially those produced from plants, have long been considered a valuable source of medicinal compounds.…”
Section: Introductionmentioning
confidence: 99%